Dynamics of Entrepreneurship and Innovation: A Bibliometric Analysis - LAHMIDI , Wiam; LAHMIDI , Zineb (Revue Internationale des Sciences de Gestion, 2026)
Over the past two decades, scholarly interest in the relationship between entrepreneurship and innovation has grown markedly, reflecting their central role in economic transformation and sustainable development. Despite this expansion, a systematic understanding of how research at their intersection has evolved over time remains limited. This study addresses this gap by examining the evolution, thematic structure, and research trajectories of entrepreneurship–innovation scholarship. A bibliometric analysis is conducted using 4,580 publications indexed in the Scopus database (2000–2025), analyzed through VOSviewer and Biblioshiny. The results reveal strong and sustained growth in scientific output, with a marked acceleration after 2015, alongside increasing international collaboration. China and the United States emerge as leading contributors, while European institutions demonstrate consistent engagement. Core themes related to entrepreneurship and innovation remain dominant, while emerging topics emphasize sustainability, education, and digital transformation. These findings highlight a field in active thematic reconfiguration, with significant implications for both theory and practice. Unlike prior reviews focused on a single dimension, this study offers an integrative and reproducible mapping of the nexus over 25 years.